Revisiting the ABC strategy: HIV prevention in Uganda in the era of antiretroviral therapy - Okware, S.; Kinsman, J.; Onyango, S.; Opio, A.; Kaggwa, P. (Postgraduate medical journal, 2005)
The ABC strategy is credited for bringing the HIV/AIDS epidemic under control in Uganda. By promoting abstinence, being faithful, and condom use, safe(r) behaviours have been identified that are applicable to people in different circumstances. However, scaling-up of antiretroviral therapy in the country raised concerns that HIV prevention messages targeting the uninfected population are not taking sufficient account of inherent complexities. Furthermore, there is debate in the country over relative importance of abstinence in reduction of HIV incidence as well as over the morality and effectiveness of condoms. The purpose of this paper is to examine each component of ABC in light of current developments. It is argued that there is still a strong justification for condom use to complement abstinence and being faithful. There is an urgent need to update and relaunch Uganda’s ABC strategy—its three elements are complementary, synergistic, and inseparable in the national HIV prevention programme.
Keywords: ABC strategy; HIV prevention; antiretroviral therapy; Uganda